A comparative study of pi and eems on emu for hybrid fuelcell power systems - Ekatiara, Cindy Reviko; Indriawati, Katherin (Faculty of Vocational Studies - Research Center, DRPM ITS, 2025)
This study investigates the Energy Management Unit (EMU) for a hybrid power system integrating PEMFC, batteries, supercapacitors, and Photovoltaic (PV) as renewable energy sources. The EMU is designed to support power supply, reduce the load on the PEMFC, and enhance operational efficiency and reliability. It intelligently manages power distribution by adjusting the use of energy sources based on system conditions, such as battery state of charge (SOC), load changes, or PV energy availability. Two types of management algorithms used in the EMU were tested: Proportional Integral (PI) and External Energy Management Strategy (EEMS). The comparison results show that EEMS outperforms PI in terms of stability and efficiency, with an average efficiency of 88.85% for EEMS compared to 88.77% for PI. Furthermore, the EEMS method demonstrates superior performance by maintaining minimal fluctuations ranging from 0.02 to 0.03, even under dynamic load conditions, while the PI method shows greater fluctuations, varying between 0.05 and 0.08.